EFEKTIFITAS PEMANFAATAN PASIR PANTAI BERKALSIUM TINGGI SEBAGAI MATERIAL PENGISI BAHAN ISOLASI RESIN EPOKSI UNTUK ISOLATOR LISTRIK - M. Toni Prasetyo (PSTE UNIMUS, 2014)
Insulation materials that commonly used in air insulation, which, is operated at high voltage, are the porcelain, glass, and polymer materials. One of the insulating polymer materials that are used is epoxy resin because it has several advantages compared to that. However, this insulation material has a degradation of the surface due to environmental and cause insulation coated with dirt and chemicals in the long time. Material that was used in this research was epoxy resin polymer isolation using of comparison values (base material diglycidyl ether of bisphenol-A: hardener material metaphenylene diamine) were 1:1, with the increase of silane and high calcium coastal sand as filler by the value of 10%, 20%, 30%, 40%, and 50%. Research was done in laboratory according to standard IEC 587: 1984. In this study, the effect of variation in stoichiometry to the hydrophobic contact angle value, leakage current waveforms, and surface degradation caused by erosion and tracking processes and tracking time were analyzed. From the results of the research, it was obtained that the epoxy resin that was used in this research are categorized as hydrofobik and partially wetted. The increase concentration of silane dan high calcium coastal sand as filler caused the increase in contact angle which meant the increase in surface insulation resistance, so that leakage currents flew on the surface not easily and slow down the aging or the degradation decreasing on the surface of insulating material. Concentration value of filler that had the optimal performance of the tracking process and erosion was 40%. Keywords : Angle of contact, epoxy resin, hidropobik, leaky current, materials filler